De Vlaamse Beweging en de patstelling van het Nederlands in de publieke overheid en het onderwijs in het jonge België (1830–1850) - Fabry, Jan (Acta Neerlandica, 2023)
Although the freedom of language use was anchored in the Belgian Constitution of 1831,in practice it led to almost complete Frenchification of public life, because civil servantscould choose their own language. Dutch thus became the language of the countryside andthe lower classes. Secondary and higher education were exclusively French speaking. TheFlemish Movement came into being as a reaction to this. Cultural associations werefounded and standards for Dutch language established. A petition in 1840 revealed theextent of the problem – the Flemish Movement demanded language equality and theestablishment of a Flemish Academy. Although there was partial success in 1850(Dutchification of primary and secondary education in Flanders), the petition alsoprovoked a hostile reaction among French speakers who accused the Flemings of antibelgitude. The Flemish Movement therefore issued a pro-Belgian manifesto. But thegovernment remained French speaking, so there was a stalemate.